Effectivenss Computational Thinking Tecniques on Student Interest to STEM Subject - Muhammad Syafiq Amin, Abdul Hamid; Eaqerzilla, Phang; Farah, Zaini (Human Resource Management Academic Research Society (HRMARS), 2024)
The purpose of this study is to investigate the impact of Computational Thinking Techniques on Student Interest to Science and Mathematics subject at schools in Sarawak. The study was conducted on two different types of data collection, online survey, and interview session. A total of 217 respondents responded been selected from teachers and student primary and secondary schools. The teachers selected based contribution on The Computationally Thinking and Computer Science (CTCS) teaching certificate program and recognized on teaching subject STEM-based. The findings can be referred to by the policymaker and Ministry of Education, Science and Technological Research (MESTR) on educational experiences in schools. We recognize that some other challenges on practice CT technique required policy to empower education system on schools in Malaysia. However, CT techniques be challenged when countries are hit by the pandemic COVID-19.